2022
DOI: 10.21608/ejbo.2022.149777.2037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Cobalt Nutrition in the Oxidative Machinery of Drought-Stressed Rice (Oryza sativa L.) Plants at the Reproductive Stage

Abstract: T HIS STUDY evaluated the impact of cobalt (Co) nutrition at the optimum concentration on growth and oxidative stress in two Egyptian rice varieties (Sakha 104 and Giza 178) under drought stress. The stress was applied at different irrigation intervals (six and eight days), and irrigation after four days was set as control through the reproductive stage. The roots and shoots parameters (lengths, and fresh and dry weights), oxidative stress biomarkers; membrane injury, lipid peroxidation, proline accumulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…MDA is a production of oxidative damage, which could reflect the degree of oxidative damage of organisms 27,28 . After R ‐Pac treated, the MDA content increased 185% compared with the control group, which was higher than that in control and S ‐Pac‐treated groups significantly (Figure 5A), which demonstrated that R ‐Pac caused severe oxidative damage to wheat.…”
Section: Resultsmentioning
confidence: 93%
“…MDA is a production of oxidative damage, which could reflect the degree of oxidative damage of organisms 27,28 . After R ‐Pac treated, the MDA content increased 185% compared with the control group, which was higher than that in control and S ‐Pac‐treated groups significantly (Figure 5A), which demonstrated that R ‐Pac caused severe oxidative damage to wheat.…”
Section: Resultsmentioning
confidence: 93%
“…The effectiveness of organic amendments in enhancing crop production is significantly augmented by the combined application with microelements (non-essential elements for plants with high potential for promoting plant growth and development at very low concentrations). Examples of these elements include boron (B), selenium (Se), cobalt (Co), titanium (Ti), silicon (Si), aluminum (Al), and vanadium (V), which play relevant roles in mastering plant growth and resistance to abiotic stresses [ [44] , [45] , [46] ]. These elements reduce the harmful effects of salinity by inducing antioxidant systems, carbohydrate content, chlorophyll content, plant biomass, and crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…The heightened presence of H 2 O 2 within various organelles of stressed seeds can lead to lipid peroxidation and loss of membrane integrity [ 72 ]. However, it can be inferred that inoculation of mycorrhizal fungi in maternal plant environment could improve proline levels and maintain the antioxidant enzyme system against drought stress while also mitigating excessive ROS accumulation [ 73 , 74 ], as reported in other species such as Zea Mays [ 71 ] and Oryza sativa [ 75 ]. Our findings showed that in comparison to L. iberica offspring, L. royleana offspring exhibited increased proline contents, higher activities of antioxidant enzymes such as SOD, CAT, and APX, and decreased H 2 O 2 accumulation, MDA, and EC.…”
Section: Discussionmentioning
confidence: 99%